2023
DOI: 10.1186/s43014-022-00112-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of probiotic fermented milk on management of obesity studied in high-fat-diet induced obese rat model

Abstract: The current study aimed to explore the hypothesis that probiotic bacteria are significantly involved in the control of obesity using Wistar rats as the test group by feeding high fat diets (HFD) induced obesity. A total of four groups of rats were considered viz., normal pellet diet fed (NC), HFD fed (DC), HFD fed rats treated with probiotic fermented milk with soy protein isolate (SPI) and whey protein concentrate (WPC) (T1), HFD fed rats treated with probiotic fermented milk without WPC and SPI (T2). Body we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…A monotonous or unbalanced diet can lead to a lack of one or another vitamin, which can subsequently lead to metabolic disorders and the occurrence of various diseases [23][24]. Therefore, it is important to know the average values required for intake with food or in the form of bioactive additives that ensure the ideal execution of the physiological and biochemical activities fixed in the human genotype [25][26].…”
Section: Resultsmentioning
confidence: 99%
“…A monotonous or unbalanced diet can lead to a lack of one or another vitamin, which can subsequently lead to metabolic disorders and the occurrence of various diseases [23][24]. Therefore, it is important to know the average values required for intake with food or in the form of bioactive additives that ensure the ideal execution of the physiological and biochemical activities fixed in the human genotype [25][26].…”
Section: Resultsmentioning
confidence: 99%
“…The study by Makwana et al [ 15 ] reported that probiotic fermented milk alone (T1) or enriched with 2% whey proteins and soy proteins (T2) and containing 10 8 –10 9 CFU/mL of lactobacilli could effectively control obesity when administered for 4 weeks to adult male Wistar rats fed with high fat diets (HFD). The fermented milks were prepared with L. helveticus MTCC V3, S. thermophilus MD2, and L. rhamnosus MTCC NS6 isolated from milk and Indian style yogurts.…”
Section: Fermented Dairy Productsmentioning
confidence: 99%
“…Liver sections stained with eosin and hematoxylin for T1 showed fewer and smaller lipid vacuoles. Viable counts of lactobacilli and S. thermophilus in feces during the feeding phase were of the order of 7 Log CFU/mL and increased progressively during the feeding period, indicating that the probiotic lactobacilli stably colonized the intestinal tract [ 15 ].…”
Section: Fermented Dairy Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intracellular and cell wall chemical components of yeast, including peptides, amino acids, fatty acids, cofactors, oligosaccharides and glycoproteins, possess positive immunomodulatory effects. Therefore, yeast may be able to exert bioactive effects like common probiotics as an additive in various industries 2 . Administration of Saccharomyces cerevisiae IFO 2346 hydrolysate to rats demonstrated a dose‐dependent decrease in body weight and fat 3 .…”
Section: Introductionmentioning
confidence: 99%